Surface treatment technology of tubular grid of lead-acid battery

By treating the pre-porous membrane mixed solution of the lead-acid battery tube grid surface, a porous loose metal lead structure is formed, which solves the problem of smooth and difficult curing of the pressure-cast tube grid surface, and improves the fast charging performance of the battery.

CN115377429BActive Publication Date: 2025-05-02ZIBO TORCH ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210698790.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-20
Publication Date
2025-05-02
Estimated Expiration
2042-06-20

AI Technical Summary

Technical Problem

The surface of the pressure cast tube-type grid for lead-acid batteries is smooth and difficult to cure. At the same time, the internal porosity and pore size of the active substance are reduced after wet extrusion paste or grouting, resulting in high curing difficulty and reduced performance.

Method used

The surface of the tube grid is treated with a mixture of pre-porous membranes. The solution includes micron-scale lead powder, magnesium dihydride, isopropylamine, carbo resin and anhydrous ethanol. After high-temperature insulation treatment in a nitrogen environment of 300-340℃, a porous loose metal lead structure is formed.

Benefits of technology

By forming a porous and loose metal lead structure, the difficulty of combining the grid and the active substance is reduced, the conductivity is improved, and the problem of smooth and difficult to cure the surface of the pressure cast tube grid for lead-acid batteries is solved. At the same time, the fast charging performance of the extruded paste tube battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003703154200000031
    Figure BDA0003703154200000031
  • Figure HDA0003703154210000011
    Figure HDA0003703154210000011
  • Figure HDA0003703154210000012
    Figure HDA0003703154210000012
Patent Text Reader

Abstract

The present invention relates to the technical field of grid surface treatment, and specifically to a process for treating the surface of a tubular grid of a lead-acid battery. The process for treating the surface of a tubular grid of a lead-acid battery comprises: after the tubular grid is impregnated with a pre-porous membrane mixed solution, it is kept warm in a nitrogen environment at 300-340°C for 0.5h-1h to obtain a tubular grid with a porous loose metal lead structure connected on the surface, that is, the surface treatment of the tubular grid is completed; the pre-porous membrane mixed solution comprises the following raw materials in weight percentage: 6-18% micron-grade lead powder, 6-18% magnesium dihydride, 6-26% isopropylamine, 0.5-2% carbopol resin, and 60-65% anhydrous ethanol. The process for treating the surface of a tubular grid of a lead-acid battery of the present invention solves the problem that the surface of the pressure-cast tubular grid used in lead-acid batteries is smooth and difficult to solidify, and at the same time significantly improves the fast charging performance of the paste-extruding tubular battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grid surface treatment, and in particular to a surface treatment process for a tubular grid of a lead-acid battery. Background Art

[0002] The tubular positive electrode structure used in lead-acid batteries effectively suppresses battery failure caused by softening and shedding of positive electrode active materials. With the requirements of environmental protection, the manufacturing method of tubular positive electrodes of lead-acid batteries has been changed from the traditional dry powder filling method to the wet paste extrusion method or grouting method.

[0003] The tubular positive grid generally adopts the casting process of pressure casting. Compared with the gravity-cast grid, the rib surface is smoother. The traditional dry powder-filled positive electrode will form a large number of large-aperture structures inside the active material in the subsequent acid-immersion process, which is conducive to the entry of oxygen during curing, strengthens the combination of the grid and the active material, and is also conducive to the diffusion of the electrolyte during the use of the battery, improving the performance of the battery. After switching to wet extrusion or grouting, the porosity and pore size inside the active material are significantly reduced, the curing is difficult, the diffusion resistance of sulfuric acid inside the active material increases sharply, and the performance decreases significantly. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a surface treatment process for tubular grids of lead-acid batteries, which solves the problem that the surface of pressure-cast tubular grids used in lead-acid batteries is smooth and difficult to solidify, and at the same time significantly improves the fast charging performance of extruded tubular batteries.

[0005] The surface treatment process of the lead-acid battery tubular grid of the present invention comprises: after the tubular grid is impregnated with the pre-porous membrane mixed solution, it is kept in a nitrogen environment at 300-340° C. for 0.5 h-1 h to obtain a tubular grid with a porous loose metal lead structure connected to the surface, thus completing the surface treatment of the tubular grid;

[0006] The pre-porous membrane mixed solution comprises the following raw materials in weight percentage: 6-18% micron-grade lead powder, 6-18% magnesium dihydride, 6-26% isopropylamine, 0.5-2% carbomer resin, and 60-65% anhydrous ethanol.

[0007] In the present invention, the preparation method of the pre-porous membrane mixed solution is as follows:

[0008] Under nitrogen environment, magnesium dihydride is dissolved in isopropylamine to obtain solution A; carbopol resin is dissolved in anhydrous ethanol to obtain solution B; solution A and solution B are mixed, stirred and dispersed at high speed, micron-grade lead powder is added, and stirred at low speed to obtain a pre-pored membrane mixed solution.

[0009] Preferably, the high-speed stirring and dispersing rate is 1800-2200 rpm, and the high-speed stirring and dispersing time is 10-30 min.

[0010] Preferably, the low-speed stirring rate is 400-500 rpm, and the low-speed stirring time is 20-30 min.

[0011] Preferably, the viscosity of the pre-pored membrane mixed solution at 25° C. is 0.05-0.1 Pa·s. The pre-pored membrane mixed solution within this viscosity range can ensure that a thin liquid differential layer is impregnated on the surface of the tubular positive grid, thereby forming a porous structure of a certain thickness.

[0012] Preferably, the lead content of the micron-sized lead powder is greater than 99.9 wt % and the average particle size is between 5 and 15 microns.

[0013] Preferably, when the tubular grid is dipped into the pre-pored membrane mixed solution, the tubular grid is completely immersed in the pre-pored membrane mixed solution for 5-10 seconds and then taken out.

[0014] In the pre-porous membrane mixed solution, the role of magnesium dihydride is to quickly release hydrogen under high temperature environment to form a porous structure; isopropylamine is used as a good solvent for magnesium dihydride to dissolve magnesium dihydride; anhydrous ethanol is used to dissolve carbopol resin to thicken the mixed solution. When micron lead powder is added, it ensures that the concentration of lead particles in all parts of the solution is uniform.

[0015] In the present invention, when the tubular grid is coated with the pre-pored membrane mixed solution, the tubular grid is completely immersed in the pre-pored membrane mixed solution for 5-30 seconds. A layer of pre-pored membrane is coated on the surface of the grid, and a porous and loose metal lead structure is connected to the smooth surface of the grid after high temperature treatment.

[0016] In the present invention, the preparation of the pre-pored membrane and the impregnation of the grid are both carried out in a nitrogen environment to avoid premature decomposition of magnesium dihydride and affect the later high-temperature pore-forming effect. The temperature of the high-temperature device is set in the range of 300°C-340°C and kept warm for 0.5h-1h to ensure the decomposition of anhydrous ethanol, isopropylamine, and carbopol resin, while the micron-sized lead powder is fused with the grid base without destroying the porous structure.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention combines the curing mechanism and the characteristics of porous lead. By connecting a layer of porous loose metal lead structure on the surface of a smooth pressure-cast grid, the difficulty of combining the grid with the active material during the curing process is reduced, the conductivity of the grid and the active material is improved, and the problem that the pressure-cast tubular grid used in lead-acid batteries has a smooth surface and is difficult to cure is solved. At the same time, the fast charging performance of the extruded tubular battery is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of the structure of the tubular grid ribs after surface treatment of the present invention;

[0020] Figure 2 The comparison is between the bonding conditions of the tubular grid ribs and the lead paste after surface treatment in Example 1 of the present invention and the bonding conditions of the tubular grid ribs and the lead paste without surface treatment; wherein a is after surface treatment, and b is without surface treatment;

[0021] Figure 3 The terminal voltage of the tubular grid after surface treatment during the battery formation simulation of Example 1 of the present invention is compared with the terminal voltage of the tubular grid without surface treatment during the battery formation simulation; wherein a is after surface treatment, and b is without surface treatment;

[0022] Figure 4 This is a cross-sectional schematic diagram of the tubular grid after being formed in Example 1 of the present invention;

[0023] In the figure: 1. Grid bars; 2. Porous lead structure layer; 3. Corrosion layer. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with embodiments, but they do not limit the implementation of the present invention.

[0025] Example 1

[0026] Preparation of pre-pored membrane mixed solution:

[0027] In a glove box, weigh 50g of magnesium dihydride powder and add it to beaker A, add 200g of isopropylamine solution, stir thoroughly until the powder is completely dissolved, and obtain solution A. Add 5g of carbomer resin to beaker B, add 490g of anhydrous ethanol, stir until the carbomer resin is completely dissolved, and obtain solution B. Mix solution A and solution B, use a high-speed dispersing device for shear stirring, the speed is 1800 rpm, after 30min, add 50g of pure lead powder with an average particle size of 10 microns, the purity is 99.9%. Adjust the speed to 400 rpm, continue stirring for 20min, until the transparency of the solution is consistent, use a viscometer to measure the viscosity of the mixed solution, the viscosity value is 0.08Pa·s.

[0028] Surface treatment of tubular grids:

[0029] In a glove box, the pressure-cast tubular traction lead-acid battery D50 positive grid was completely immersed in the pre-porous membrane mixed solution for 5 seconds, then taken out and quickly placed in a 300°C high-temperature device filled with nitrogen and kept warm for 0.5 hours to obtain a tubular grid with a porous loose metal lead structure connected on the surface, thus completing the surface treatment of the tubular grid.

[0030] The performance indicators of the surface treated tubular grid and the untreated tubular grid were tested and compared, as follows:

[0031] (1) Combine the surface treated grid and polyester tube, and set the apparent density to 3.8g / cm 3 The positive lead paste is squeezed into the cavity between the grid ribs and the row pipes, and enters the curing device for curing to obtain the plate. The curing and drying methods are shown in Table 1:

[0032] Table 1 Curing and drying process parameters

[0033]

[0034] After curing, the plate was dissected to observe the bonding between the treated grid bars and the lead paste, and compared with the bonding between the grid bars and the lead paste without surface treatment. Figure 2 .from Figure 2 It can be seen that after the grid is surface treated by the treatment method of the present invention, a good connection is established between the ribs and the lead paste during curing, and more lead paste is attached to the surface of the ribs, reducing the difficulty of curing.

[0035] (2) The surface treated grids of the present invention are assembled into a plate to simulate a battery, the method is as follows:

[0036] Two groups of simulated batteries were assembled by using one D50 positive electrode plate assembled with the grid after the surface treatment of the present invention and two D50 negative electrode plates for traction lead-acid batteries, and the negative electrode plates were coated with PE polyethylene separators. The distance between the positive electrode plate and the negative electrode plates on both sides was 1 cm, and 1.06 g / ml sulfuric acid electrolyte was perfused for formation.

[0037] At the same time, a reference simulated battery was prepared as follows:

[0038] One D50 positive electrode plate manufactured by the traditional extrusion method and two D50 negative electrode plates for traction lead-acid batteries were assembled into two groups of simulated batteries. The negative electrode plates were coated with PE polyethylene separators. The distance between the positive electrode plate and the negative electrode plates on both sides was 1 cm. 1.06 g / ml sulfuric acid electrolyte was perfused for formation.

[0039] The above two simulated batteries are formed as follows:

[0040] Step 1: 3A, 1h;

[0041] Step 2: 10A, 4h;

[0042] Step 3: 6A, 15h.

[0043] The terminal voltages of the two simulated batteries during formation are shown in Figure 2. Figure 3 .from Figure 3It can be seen that for the grid treated by the surface treatment process of the present invention, the simulated battery terminal voltage is significantly lower than that of the reference electrode during formation, indicating that the electronic connection performance between the ribs and the lead paste is good, which reduces the polarization of the electrode during formation.

[0044] (3) The cross section of the grid ribs after the surface treatment process of the present invention is observed. Figure 4 .from Figure 4 It can be seen that the rib surface has a rough surface, and the outside of the rough surface is connected to the corrosion layer formed during the chemical formation.

[0045] (4) The electrolyte of a group of simulated batteries of the present invention and a reference simulated battery was quickly replaced with a 1.28 g / ml sulfuric acid electrolyte, and a discharge test was performed after supplementary charging for 4 hours using a current of 3.5 A.

[0046] Capacity test:

[0047] 10A discharge, end voltage 1.70V, then switch to normal charging;

[0048] 50A(1C) discharge, end voltage 1.50V, then switch to normal charging.

[0049] The normal charging method is: 7A charging, after limiting the voltage to 2.4V, switch to 3.5A charging for 12h.

[0050] Charge acceptance test:

[0051] The charged battery was discharged again at 10A, and after the termination voltage reached 1.70V, it was charged with a high current of 50A. The time for the battery terminal voltage to reach 2.45V was recorded to examine the battery's charging acceptance capacity.

[0052] Resistance test:

[0053] The fully charged simulated battery resistance was tested using the American Arbin equipment, with the following parameter settings:

[0054] Pulse current 10A, time 5ms.

[0055] The test results are shown in Table 2.

[0056] Table 2 Simulated battery test results

[0057] name Simulated battery of the present invention Reference Simulated Battery 10A discharge time / h 6.5 6.6 50A(1C) discharge time / min 55 49 50A charging to reach 2.45V time / h 45 33 Resistance / mΩ 1.5 3.9

[0058] It can be seen from Table 2 that the 10A discharge capacity of the simulated battery of the present invention is comparable to that of the reference, but the large current 1C discharge performance, charge acceptance and resistance are all better than those of the reference simulated battery.

[0059] Example 2

[0060] Preparation of pre-pored membrane mixed solution:

[0061] In a glove box, weigh 100g of magnesium dihydride powder and put it into beaker A, add 50g of isopropylamine solution, and stir thoroughly until the powder is completely dissolved to obtain solution A. After putting 10g of carbomer resin into beaker B, add 400g of anhydrous ethanol and stir until the resin is completely dissolved to obtain solution B. Mix solution A and solution B, and use a high-speed dispersing device to shear and stir at a speed of 2200 rpm. After 10min, add 100g of pure lead powder with an average particle size of 15 microns and a purity of 99.9%. Adjust the speed to 500 rpm and continue stirring for 30min until the transparency of the solution is consistent. Use a viscometer to measure the viscosity of the mixed solution, and the viscosity value is 0.075Pa·s.

[0062] Surface treatment of tubular grids:

[0063] In a glove box, the pressure-cast tubular traction lead-acid battery D50 positive grid was completely immersed in the pre-porous membrane mixed solution for 10 seconds, then taken out and quickly placed in a 340°C high-temperature device filled with nitrogen and kept warm for 1 hour to obtain a tubular grid with a porous loose metal lead structure connected on the surface, thus completing the surface treatment of the tubular grid. A total of 27 pieces of the grid were prepared.

[0064] The performance indicators of the surface treated tubular grid and the untreated tubular grid were tested and compared, as follows:

[0065] The surface treated grid and polyester tube are combined to make the apparent density 3.82g / cm 3 The positive electrode lead paste is squeezed into the cavity between the grid ribs and the row pipes, and enters the curing device for curing to obtain the electrode plate. The curing and drying methods are shown in Table 1.

[0066] A paste-extruded tube positive electrode plate prepared using the surface-treated grid of the present invention was used to assemble three D-450 traction lead-acid batteries with a 9-positive and 10-negative electrode group structure. The design of PE separator covering the negative electrode was used and compared with the traditional paste-extruded D-450 lead-acid battery after formation.

[0067] The above two types of batteries are formed in the same batch using an acid circulation formation method, and the acid circulation method is as follows:

[0068] First, open the acid circulation low-density system and adjust the density of the low-density electrolyte to 1.060g / cm 3 -1.080g / cm 3Within the range, the battery filling port is connected to the acid circulation connector. At this time, the low-density electrolyte density flows into the single battery through the connector to start acid filling. After the acid filling is completed, circulate and soak for 2 hours, then start the acid circulation system to connect the power supply to start charging, and start the formation equipment control program in the computer to charge and form. During the low-density circulation process, the low-density electrolyte density in the high-level acid tank flows into the acid circulation system through a certain pressure, and the acid circulation system flows into the acid circulation connector acid inlet pipe through the acid inlet pipe, thereby entering the battery, and then returns to the acid return pipe from the acid circulation connector acid return pipe, and then flows into the low-level tank.

[0069] When the acid circulation formation program runs to the last stage, close the low-density acid circulation system, open the high-density acid circulation system, and start circulating acid. Adjust according to the measurement results until the acid density reaches (1.290±0.005)g / cm 3 (30℃) and remain stable for 0.5h. The acid circulation charging stage is over, the cooling system is turned off, and the acid circulation connector is removed.

[0070] Performance tests were performed on two types of batteries:

[0071] (1) 5 hr capacity test, discharge current 90A, end voltage 1.7V, record discharge time;

[0072] (2) High rate discharge test: discharge at 450A, termination voltage at 1.5V, and record discharge time;

[0073] (3) High current charging test: charge at 450A (1C), record the time it takes to reach 2.45V, and record the electrolyte temperature in the battery.

[0074] (4) Resistance test: perform resistance test on the charged battery. Parameter setting:

[0075] Pulse current 30A, time 5ms.

[0076] The test results are shown in Table 3.

[0077] Table 3

[0078] project Reference Cell This application battery 5hr discharge time / h 4.98h 5.19h 450A discharge time / min 37 46 1C charging reaches 2.45V time / min 36 42 Maximum temperature during 1C charging / ℃ 38.5 33 Resistance / mΩ 11.5 7.6

[0079] It can be seen from Table 3 that the battery of the present invention has better high current 1C discharge performance, charge acceptance and resistance than the reference simulation battery.

Claims

1. A surface treatment process for a lead-acid battery tubular grid, characterized in that: After the tubular grid is impregnated with the pre-porous membrane mixed solution, it is kept in a nitrogen environment at 300-340°C for 0.5h-1h to obtain a tubular grid with a porous loose metal lead structure connected on the surface, thus completing the surface treatment of the tubular grid; The pre-porous membrane mixed solution comprises the following raw materials in weight percentage: 6-18% micron-grade lead powder, 6-18% magnesium dihydride, 6-26% isopropylamine, 0.5-2% carbomer resin, and 60-65% anhydrous ethanol; The preparation method of the pre-porous membrane mixed solution is as follows: Under nitrogen environment, magnesium dihydride is dissolved in isopropylamine to obtain solution A; carbopol resin is dissolved in anhydrous ethanol to obtain solution B; solution A and solution B are mixed, stirred and dispersed at high speed, micron-grade lead powder is added, and stirred at low speed to obtain a pre-pored membrane mixed solution.

2. The surface treatment process of the lead-acid battery tubular grid according to claim 1, characterized in that: The high-speed stirring and dispersion rate is 1800-2200 rpm.

3. The surface treatment process of the lead-acid battery tubular grid according to claim 1, characterized in that: The high-speed stirring and dispersing time is 10-30min.

4. The surface treatment process of the lead-acid battery tubular grid according to claim 1, characterized in that: The low speed stirring rate is 400-500 rpm.

5. The surface treatment process of the lead-acid battery tubular grid according to claim 1, characterized in that: The low speed stirring time is 20-30 minutes.

6. The surface treatment process of the lead-acid battery tubular grid according to claim 1, characterized in that: The viscosity of the pre-porous membrane mixed solution at 25° C. is 0.05-0.1 Pa·s.

7. The surface treatment process of the lead-acid battery tubular grid according to claim 1, characterized in that: The lead content of the micron-grade lead powder is greater than 99.9wt%, and the average particle size is between 5 and 15 microns.

8. The lead-acid battery tubular grid surface treatment process according to claim 1, characterized in that: When the tubular grid is dipped into the pre-pored membrane mixed solution, the tubular grid is completely immersed in the pre-pored membrane mixed solution for 5-10 seconds and then taken out.

Citation Information

Patent Citations

  • Production process of storage battery positive plate

    CN110690454A

  • Deep-cycle long-life lead-acid storage battery lead paste for parking, battery thereof and manufacturing process method of battery

    CN113675397A